1986
DOI: 10.1038/icb.1986.20
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC ANALYSIS OF KUNJIN VIRUS ISOLATES USING HAEIII AND TAQI RESTRICTION DIGESTS OF SINGLE‐STRANDED cDNA TO VIRION RNA

Abstract: Summary. The genotypic relatedness of 15 Kunjin (KUN) virus isolates from widely separated geographic regions in Australia was examined at the molecular level. Haelll and TaqI restriction digest profiles of cDNA transcribed from virion RNA revealed a close genetic similarity between all isolates. We estimate that the nucleotide sequence divergence between any pair of KUN . isolates is probably less than 1%. We conclude that a single KUN genetic type has existed in enzootic and epizootic areas of virus activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…An evolutionary link between KUN and WN viruses may persist in Southeast Asia because KUN virus has been isolated from mosquitoes in Borneo (Bowen et al, 1970). However, the evolution of KUN virus within Australia has been slow; the nucleotide divergence between any pair of KUN virus isolates is 'probably less than 1 ~' (Lobigs et al, 1986). It is of interest that large domains of high homology, 94~ and 87~, persist in the KUN and WN sequences within the 5' and 3' non-coding regions, respectively, suggesting common structural or functional purposes.…”
Section: Discussionmentioning
confidence: 99%
“…An evolutionary link between KUN and WN viruses may persist in Southeast Asia because KUN virus has been isolated from mosquitoes in Borneo (Bowen et al, 1970). However, the evolution of KUN virus within Australia has been slow; the nucleotide divergence between any pair of KUN virus isolates is 'probably less than 1 ~' (Lobigs et al, 1986). It is of interest that large domains of high homology, 94~ and 87~, persist in the KUN and WN sequences within the 5' and 3' non-coding regions, respectively, suggesting common structural or functional purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Although differences might exist in the distribution of MVE and KUN, that is the latter virus has been found more frequently in the south-east of Australia, KUN also has one topotype which can be found throughout Australia. Lobigs et al (1986) demonstrated genetic homogeneity of KUN isolates, but the sensitivity of restriction enzyme mapping relative to fingerprinting was in doubt (Marshall, 1988). Therefore it was not clear whether the perceived dissimilarity of the distribution of geographical varieties between SLE and KUN was due to technical differences.…”
Section: -9008 © 1989 Sgmmentioning
confidence: 99%
“…One topotype was found throughout Australia, which was in contrast to the findings with Saint Louis encephalitis virus (SLE) (Trent et al, 1981). Lobigs et al (1986) examined the genetic relatedness of 15 KUN isolates by comparing the HaelII and TaqI restriction digest profiles of cDNA to virion RNA. Their data, when subjected to mathematical analysis, revealed a maximum sequence divergence of less than 1 ~ between isolates.…”
mentioning
confidence: 99%
“…Purified virus was prepared using a modification of the method described by Lobigs et al (1986). Briefly, Vero cell monolayers, grown to confluence under SCC in 850 cm 2 roller bottles (Coming) were infected with WNV at an m.o.i, of 10.…”
Section: Micementioning
confidence: 99%